Organic matter and size distribution transformations during a simulated bulk phase of sewer transport - Gardner, Paul (University of Ottawa (Canada), 2003)
As wastewater is transported in a sewer system, in-sewer transformations occur that allow the sewer system to be considered as a pipeline reactor. Domestic wastewater from the local wastewater treatment facility was monitored for a 3 day period to simulate the bulk phase of sewer flow. Aerobic and anoxic reactive environments were studied to determine the change in organic matter and size distribution. Aerobic and anoxic conditions showed similar treatment of organic matter with an average of 55% of the total chemical oxygen demand (CODt) removed in 72 hours. The CODt consumption rate increased to a mean maximum of 8.4 mg/L/h a mean experiment time of 24 hours. The majority of the organic removal occurred in the first 42 hours. Aerobic conditions led to the formation of larger microbial flocs than anoxic conditions demonstrated by an increasing trend of mean area particle diameter (D a) with the mean increase 8 microns compared to a 3 micron decrease for anoxic conditions. Initial substrate and biomass quality strongly influenced the observed transformations.
Keywords: Engineering, Chemical.; Engineering, Electronics and Electrical.